Cytotoxicity and Structural Analyses of 2, 2′‐Bipyridine‐, 4, 4′‐Dimethyl‐2, 2′‐bipyridine‐ and 2‐(2′‐Pyridyl)quinoxalineplatinum(II) Complexes. Issue 25 (September 2015) - Pages, Benjamin J.; Zhang, Yingjie; Li, Feng; Sakoff, Jennette; Gilbert, Jayne; Aldrich‐Wright, Janice R.
Abstract: Invited for the cover of this issue is the group of Janice Aldrich‐Wright at the University of Western Sydney, Australia. The cover image shows X‐ray crystal structures and CD spectra of platinum(II) complexes of 4, 4'‐dimethyl‐2, 2'‐bipyridine and 2‐(2'‐pyridyl)quinoxaline against a background of fluorescently stained HT29 human colon carcinoma cells. The Southern Cross refers to the country of origin of this work. Abstract : We recently developed complexes of dipyridoquinoxaline with high anticancer activity... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 4167 ff .